CARA MENGATASI KESULITAN BELAJAR MATEMATIKA OPERASI HITUNG PERKALIAN DAN PEMBAGIAN DENGAN METODE JARIMATIKA PADA ANAK SEKOLAH DASAR - Cahyani, Shofi Yulia; Widodo, Slamet (Journal of Professional Elementary Education, 2024)
The purpose of this study is 1) to find out the factors that cause Ayesha Khairatun Hisan difficulties in operating multiplication and division calculations. 2) how to learn how to use so far in operating multiplication and division calculations. This type of research is descriptive qualitative research with case study method. The subject of this study was Ayesha Khairatun Hisan, class IV SDIT Insantama Malang. Data collection techniques used in this study are observation, interviews, and documentation. The data collected in the case studies are comprehensive and integrated. This study discusses a case study about the difficulties of learning mathematics in multiplication and division arithmetic operations with teaching process techniques. This research was conducted to solve problems that occur during teaching and learning activities by applying learning models in order to get solutions to these problems. The results of this study are 1) the causes of difficulties in operating multiplication and division calculations, namely being less thorough and focused in working on problems so that mathematics lessons in multiplication and division arithmetic operations are considered difficult. 2) The method used so far is quite difficult to understand, so the Jarimatika method is a solution in operating multiplication and division calculations